2022
DOI: 10.3390/plants11152049
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria-Mediated Immune Responses in Pepper Plants against Fusarium Wilt

Abstract: Research in plant pathology has increasingly focused on developing environmentally friendly, effective strategies for controlling plant diseases. Cyanobacteria, including Desmonostoc muscorum, Anabaena oryzae, and Arthrospiraplatensis, were applied to Capsicum annuum L. to induce immunity against Fusarium wilt. Soil irrigation and foliar shoots (FS) application were used in this investigation. The disease symptoms, disease index, osmotic contents, total phenol, Malondialdehyde (MDA), hydrogen peroxide (H2O2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 70 publications
2
10
0
Order By: Relevance
“…Also, the frequent use of chemical pesticides has revealed many problems in plant, human, and animal health. It is now necessary for researchers to try to reach biological methods as safe alternatives to the use of chemical pesticides (Abdelaziz et al 2022a ; Attia et al 2016 ). Previous studies have proven that the use of plant growth-promoting microorganisms has a significant anti-microbial effect in addition to stimulating the plant’s physiological immunity, which is beneficial to increasing productivity (Attia et al 2022a , 2022b ; Abd Alhakim et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the frequent use of chemical pesticides has revealed many problems in plant, human, and animal health. It is now necessary for researchers to try to reach biological methods as safe alternatives to the use of chemical pesticides (Abdelaziz et al 2022a ; Attia et al 2016 ). Previous studies have proven that the use of plant growth-promoting microorganisms has a significant anti-microbial effect in addition to stimulating the plant’s physiological immunity, which is beneficial to increasing productivity (Attia et al 2022a , 2022b ; Abd Alhakim et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under fungal infection, plants accumulate osmolytes such as proline that act as osmoregulator to scavenge reactive oxygen species [78]. The increase of proline contents in infected pepper plants was similarly to that in heavy studies [21,79]. In addition, stressed plants treated with fungal endophytes (such as Piriformospora indica and Aspergillus ochraceus) have low levels of proline in comparison with non-treated plants [80].…”
Section: Discussionmentioning
confidence: 82%
“…Plant physiological immunity can be stimulated by many means, perhaps the most important of which are growth-stimulating organisms against stress [3,18,19]. The harmful effect of Fusarium wilt can be minimized by the induction of natural exogenous inducers such as phytohormones and antioxidant molecules [20][21][22]. Furthermore, the molecules extracted from endophytes have been reported to be powerful biostimulants of growth, physiological immunity, and yield, as they enhanced tolerance to environmental stress by stimulating the antioxidant system and improving nutrient availability and nutrient uptake from the soil [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Heavily recently studies demonstrated that fungal plant diseases caused significant changes in vegetative growth [ 82 , 83 , 84 ]. Results in Figure 6 shows A. solani affected greatly reduced eggplant growth traits; shoot length, root length and number of leaves by 50.96%, 48.27% and 34.89%.…”
Section: Resultsmentioning
confidence: 99%